Students' perceptions of learning critical thinking in college English reading courses through traditional classroom lectures - Huang, Qiuyang; Muhamad, Mohd Mokhtar; Che Nawi, Nur Raihan (Human Resources Management Academic Research Society (HRMARS), 2024)
This qualitative study investigates college English reading students' opinions of traditional classroom lectures, paying particular attention to how these lectures affect the growth of critical thinking. Six college students participated in semi-structured interviews for this study, which looks at their opinions on the general benefits and drawbacks of traditional lecturebased instruction. The results show that although students value the methodical information transfer and professional direction offered by traditional lectures, they also point out important disadvantages including passive learning and a lack of engagement, which impede the development of critical thinking. Based on their learning preferences, educational experiences, and course requirements, students' perceptions range significantly, according to the study. These insights enhance our knowledge of the ways in which traditional lecture techniques affect critical thinking in English reading courses and point out areas in which pedagogical innovation is needed to better support the development of critical thinking abilities. There includes a discussion of suggestions for future research directions and teaching practices.